The Learning Process of The Rapa'i Geleng Dance At Seulawet Arts Groups in UIN AR-RANIRY Banda Aceh - Umul Aiman; Uliyana Uliyana; Novysa Basri; Novita Hidayani; Rizki Rahmad; Vinny Aryesha; Aris Munandar (Universitas Negeri Semarang, 2024)
Although dances are generally performed by women, the traditional Acehnese dance